Groundwater and surface water interaction for integrated catchment planning - Aradas, Rodolfo D. (2005)
Integrated Catchment Management (ICM), defined as the design of intervention strategies encompassing and integrating the fields of hydrology, environmental, social and economic science, is vital in order to reach sustainable solutions on a catchment basis. Modelling lies at the core of the ICM process as it supports baseline studies and enables analysis of proposed intervention measures both for present day conditions and under future scenarios. Its core role in ICM leads to the need to develop modelling into a more comprehensive activity within which the design of a modelling approach, selection of tools and need for linkages can be thoughtfully matched to the requirements of ICM. Initial research revealed a gap in this area, leading to development of a Framework for Catchment Modelling Studies (FCMS) intended to create a staged and systematic approach that could be used as a template for development of modelling exercises that strike the right balance between ICM needs, project costs and the availability of human and technical resources. To demonstrate the utility of the FCMS and populate it with application guidance, practical techniques and examples, technical research was focused on analysis of groundwater-surface water interaction in the Rio Salado Basin. This flatland of 175,000km2, is located in the Buenos Aires Province of Argentina and features widespread groundwater-surface water interaction as the key driver of the flooding in vast areas of the basin. This flooding currently limits the potential for agricultural and livestock development of what is, economically, most important region of the country. Research revealed that use of uncoupled groundwater-surface water models was inadequate to simulate observed flooding in a test area of the Rio Salado Basin, and a new program - iSISMOD - was developed by coupling MODFLOW (McDonald and Harbaugh, 1988) with ISIS (HR Wallingford and Halcrow, 1995) to permit dynamic coupling of both systems and support improved flood probability mapping. The research concludes that adoption of an FCMS approach would provide scientists and engineers with a systematic basis from which to think through technical issues involved in the modelling cycle, and would facilitate improved decision making on key issues, such as when uncoupled models must be replaced by coupled models. This systematic approach is not only resource-effective, it is more importantly essential to support development of integrated catchment management plans that are sustainable.